Asymptotic solution for a scattered field by cylindrical objects buried beneath a slightly rough surface. Issue 2 (1st June 2012) - Fiaz, M.A.; Frezza, F.; Pajewski, L.; Ponti, C.; Schettini, G.
ABSTRACT: The problem of scattering of electromagnetic waves from a set of cylindrical objects buried beneath a slightly rough surface is undertaken with the cylindrical wave approach as a method of analysis. The small perturbation method is used to compute the scattered field from a rough surface. Numerical results for a rough surface with a sinusoidal profile are obtained with asymptotic evaluation.